Workload Analysis Using the Full Time Equivalent (FTE) Method to Optimizing Labor - Hendra Kurniawan; Yulianah Yulianah; Rizkiana Karmelia Shaura (Institute of Computer Science (IOCS), 2022)
The purpose of this study was to determine how the workload of the legal settlement unit and its supporting units and to determine the optimal number of workers at PT Telkom Indonesia (Persero), Tbk. This study uses the Full Time Equivalent (FTE) method, a workload analysis method that measures the length of time for completion of work. Based on the results of research using the FTE method, it is known that there is an imbalance in the workload of 8 units. Where there are 6 units with excessive workloads including the Legal settlement unit, 3 proposed workers are needed, Telkom regional 3 needed 7 proposed workers, Telkom regional 4 needed 4 workers, Telkom regional 5 needed 3 proposed workers, Telkom regional 6 needed 2 workers proposed work, and telkom regional 7 needed 2 proposed workers, while only 2 units had a normal (fit) workload, namely regional telkom 1 and 2. The result is that the total workload on all units can be carried out by 42 workers. And then the workload balance value is greatly increased from the previous 5% to 80%.